Detection of brucella melitensis in blood samples collected from goats - Al-Garadia, Maged Ahmed; Bejo, Siti Khairani; Zakaria, Zunita; Omar, Abdul Rahman (2011)
PCR assays have been shown to be a promising option for the diagnosis of brucellosis. However, there is no study conducted in Malaysia to identify the brucellosis in goat’s population. In this study three whole blood samples and sera were collected from goat’s farm in Kedah state Malaysia which was suspected to have brucellosis. Serological and molecular detection of brucellosis have been done including RBPT, CFT, conventional PCR and Real time. The evaluation of each test have been discussed rather than the sensitivity and specificity of the each test which can be used in Malaysia national eradication programs. In conclusion, the combination between the serological test and molecular technique specially real time PCR depend on IS711 region in hypothetical protein is promising and can be reduced to false positive result which can cause heavy economical loss during controlling programs.